Surgical aortic valvuloplasty after balloon valvuloplasty in neonates and infants - Chornenka, I. (Ukrainian Journal of Cardiovascular Surgery, 2018)
The management of patients with critical aortic stenosis is a complex and difficult problem of cardiac surgery, which is constantly debated. Critical aortic stenosis in infants and newborns is a complex pathology that requires urgent interventions. Objective. Analyze the results of surgical treatment of patients of the first year of life with isolated aortic stenosis after preliminary balloon valvuloplasty. Materials and methods. For the period from 2009 to 2015, 11 babies with aortic stenosis were selected, operation has been performed for these children after balloon valvuloplasty. For the period of balloon valvuloplasty, the average age of patients was 18.5±19.4 days (0 to 62 days), the average body weight was 3.6±1.1 kg (2.3 to 6.3 kg). For the period of surgical valvuloplasty, the average age of patients was 134±91.5 days (from 33 to 351 days). The average weight was 6.8±2 kg (from 3.4 to 9.9 kg). Results and discussion. Within a year after balloon valvuloplasty, the pressure gradient on the aortic valve increased to the baseline level. After surgical correction, there were good direct and medium long-term results relative to the gradient on the aortic valve. In the mid-term period, all patients were diagnosed with aortic valve insufficiency. There was no immediate and long-term mortality after surgical correction in the study group of patients. Conclusions. The analysis of immediate and medium-term results of surgical aortic valvuloplasty after balloon valvuloplasty in infants showed a significant progression of aortic insufficiency in the medium long-term period and a high percentage of reoperations. Freedom from reoperations was 72.7% during 4 years of follow up.